Formation of Employee Discipline Character Through the Implementation of Talenta’s Human Resource Information System at PT. Pelayaran Tamarin Samudra Tbk . - Yeni Pariyatin (Jurnal Ilmu Sosial Politik dan Humaniora (Jisora), 2022)
Currently, many companies have used information technology as a medium to support the achievement of organizational goals and PT. Pelayaran Tamarin Samudra Tbk. Previously, this company had utilized information technology in its team member attendance system, namely, by applying a fingerprint attendance device; this tool was less effective and efficient because the type of business carried out in this company was a field, namely shipping. This study aims to analyze team member discipline by applying the Human Resource Information System at PT. Pelayaran Tamarin Samudra Tbk. This type of research is descriptive with a qualitative approach, assisted by quantitative data obtained from distributing questionnaires and observations. In determining the sample, the author uses a random sampling technique. From the total population of employees, as many as 200 people took 40 people as samples. Analysis of the data through the stages of qualitative descriptive data with percentages and descriptions of the explanation of the primary data resulting from the distribution of the questionnaire. The results showed team member work discipline by applying the Human Resource Information System Talents at PT. Pelayaran Tamarin Samudra Tbk. Already effective. The study's conclusion states that the factors that shape the character of work discipline in the company, namely leadership examples, respect, fairness, and firmness, have been carried out well, only for the factors of supervision and sanctions that need to be improved again.